Houseways in southern Oman - Risse, Marielle, author.
1 online resource
Keywords: "This book explores how houses are created, maintained and conceptualized in southern Oman. Based on long-term research in the Dhofar region, it draws on anthropology, sociology, urban studies and architectural history. The chapters consider physical and functional aspects, including regulations governing land use, factors in siting houses, architectural styles and norms for interior and exterior decorating. The volume also reflects on cultural expectations regarding how and when rooms are used and issues such as safety, privacy, social connectedness and ease of movement. Houses and residential areas are situated within the fabric of towns, comparison is made with housing in other countries in the Arabian peninsula, and consideration is given to notions of the 'Islamic city' and the 'Islamic house'. The book is valuable reading for scholars interested in the Middle East and the built environment"--